1991
DOI: 10.1144/gsjgs.148.5.0813
|View full text |Cite
|
Sign up to set email alerts
|

A guide to stratigraphical procedure

Abstract: The continuing development of stratigraphical concepts and the application of new methods has led the Stratigraphy Committee of the Geological Society of London to present a new guide to stratigraphical procedure. Some of the principal types of stratigraphy are outlined and guidelines and recommendations are given on procedure, practice and terminological usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(30 citation statements)
references
References 29 publications
0
29
0
1
Order By: Relevance
“…Intense study of these species has allowed their biostratigraphy to be plotted (Hart et al, 1989) and foraminiferal species assemblages to be identified and 'dated' by comparison to known Species Assemblage Biozones from the literature (cf. Whittaker et al, 1991;Lowe and Walker, 1997). The stratigraphy and structure of the Chalk in England are well known (Peake and Hancock, 1978;Wood and Smith, 1978;Mortimore and Pomerol, 1987) and these data have allowed the outcrop morphology of the different biostratigraphically defined Chalk stages to be mapped ( Figure 2).…”
Section: Biostratigraphymentioning
confidence: 98%
“…Intense study of these species has allowed their biostratigraphy to be plotted (Hart et al, 1989) and foraminiferal species assemblages to be identified and 'dated' by comparison to known Species Assemblage Biozones from the literature (cf. Whittaker et al, 1991;Lowe and Walker, 1997). The stratigraphy and structure of the Chalk in England are well known (Peake and Hancock, 1978;Wood and Smith, 1978;Mortimore and Pomerol, 1987) and these data have allowed the outcrop morphology of the different biostratigraphically defined Chalk stages to be mapped ( Figure 2).…”
Section: Biostratigraphymentioning
confidence: 98%
“…Event diachronic stratigraphy (Whittaker et al, 1991;Lowe and Walker, 1997) is a category of composite interpretational stratigraphy that refers to short-term phenomena that left some trace in the geological records. In the case of alluvial filling in foredeep and foreland basins, climate changes and man activities represent the main driving events for hydrodynamical changes of rivers.…”
Section: Integrated Stratigraphymentioning
confidence: 99%
“…In many instances these two different approaches are used in tandem. Lithostratigraphical nomenclature often comprises type locality or area, lithology and unit term (Hedberg 1976;Whittaker et al 1991); for example, the London Clay Formation. However, lithology can be, and often is, omitted.…”
Section: Methodology Used For Interpreting the Engineering Geologicalmentioning
confidence: 99%